Effect of educational training on nutrition and weight control in under-18 Spanish wrestlers - Andrea Visiedo; Jose Manuel Palao
Abstract The aim of this study was to investigate the effect of a formative program concerning nutrition, weight control, and its risks wrestlers under the age of 18 (under-18) at the Spanish national level. The sample comprised 36 under-18 wrestlers that were pre-selected for the Spanish national team. A quasi-experimental design with a pre-test and post-test was used. The dependent variableswere the knowledge of nutrition and weight control and its risks. The independent variable was the educational program. The program had three 30-minute sessions that combined talks, videos, and tasks to complete. Descriptive and inferential analyses were done (t-test, Wilcoxon test). Results indicate that the educational program was effective at increasing under-18 wrestlers' knowledge about weight control and its risks,but was ineffective with regard to nutrition knowledge. The paper concludes with a discussion regarding the effect of the intervention program, the difficulties with including this type of knowledge and skill in the preparation of combat sport athletes, and the need for further research in this area.